2017
DOI: 10.3991/ijep.v7i4.7433
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Test for Assessing Incoming Students’ Cognitive Competences

Abstract: Abstract-Every year, a few weeks after new freshmen students started on their course of studies in Computer Science, many lecturers complain that some of their students are ill-equipped with those competences that are necessary to study successfully. Hence, these students struggle. This situation can be observed universally, at different universities and in various countries. On the other hand, at the same time there usually are some students around, which meet study requirements rather easily. To effectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The limitations of Al-Emran and Salloum's research (2017) were it didn't yet show in detail the items of the instruments were used to evaluate the instructor's performance. Research that was conducted by Thurner et al (2017) showed the existence of forms of cognitive tests that were used to assess students' initial abilities, mathematics abilities, and computer skills as a basis for knowing their readiness before learning further competencies. The limitations of Thurner et al's research (2017) were it didn't yet show the calculation of validity and reliability of the items that were used to test students' initial cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of Al-Emran and Salloum's research (2017) were it didn't yet show in detail the items of the instruments were used to evaluate the instructor's performance. Research that was conducted by Thurner et al (2017) showed the existence of forms of cognitive tests that were used to assess students' initial abilities, mathematics abilities, and computer skills as a basis for knowing their readiness before learning further competencies. The limitations of Thurner et al's research (2017) were it didn't yet show the calculation of validity and reliability of the items that were used to test students' initial cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%
“…(2) There should be more opportunities to contact and share information among colleagues. (3) The result of following the first two steps mentioned above is that after some time, the teaching skills of the teachers keep improving year after year and they succeed in teaching statistics from an applied point of view and thereby improving the student's performance [52,53,54,55,56].…”
Section: Resultsmentioning
confidence: 99%
“…But they must also cultivate decision making, planning, and contextual research skills. These skills will enable future industrial engineers to be entrepreneurs [12], to feel capable of building businesses, and to foster employability [26]. Among these skills, the proposed context research competency can be developed through research, national reality, and history courses, which are often replaced by specialty courses.…”
Section: Post-covid-19 Industrial Engineering Career Curriculummentioning
confidence: 99%